Kinerja Karyawan Hotel POP Bandar Lampung Dilihat dari Disiplin kerja dan Pelatihan kerja - Yohanson A.K.; Lukmanul Hakim; Yulian Wijaya (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
This study aims to determine the effect of work discipline on employee performance at POP Bandar Lampung hotels, to determine the effect of job training on employee performance at POP Bandar Lampung hotels and to determine the effect of work discipline and job training on employee performance at POP hotel in Bandar Lampung. This type of research used in this research is a type of quantitative research using the associative method. The data source used is primary data. The data collection method used field research (field research). The population in this study amounted to 46 employees. The sampling method in this study is non-probability and uses purposive sampling technique. Respondents in this study were 40 employees. Test the instrument requirements using the validity test and reliability test. The data analysis requirements test used in this study were the linearity test and the multicollinearity test. Methods of data analysis using multiple linear regression analysis and the use of hypotheses using the t test and F test. The results of this study indicate that Work Discipline affects the Employee Performance of Hotel POP Bandar Lampung. Job Training has an effect on the Employee Performance of Hotel POP Bandar Lampung and collectively Work Discipline and Job Training have an effect on the Employee Performance of Hotel POP Bandar Lampung.